Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Stres Kerja Sebagai Variabel Intervening pada Dinas Bina Marga Cipta Karya dan Tata Ruang Prov. Sumatera Barat - Lutfia Lutfia; Dorri Mittra Candana; Agam Mei Yudha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to test how much influence workload and work environment have on employee performance with work stress as an intervening variable at the Department of Highways, Cipta Karya and Spatial Planning, West Sumatra Province. The sample in this study consisted of 53 respondents. The population in this study were employees of the Secretariat of the Department of Highways, Cipta Karya and Spatial Planning, West Sumatra Province. (1) There is a positive and significant influence between Work Load and Work Stress at the Department of Highways, Cipta Karya and Spatial Planning. (2) There is a positive and significant influence between the Work Environment on Job Stress at the Bina Marga Cipta Karya and Spatial Planning Service. (3) There is a positive and significant influence between Workload on Employee Performance at the Highways, Cipta Karya and Spatial Planning Services. (4) There is no positive and significant influence between the Work Environment and Employee Performance at the Bina Marga Cipta Karya and Spatial Planning Service. (5) There is a positive and significant influence between Job Stress on Employee Performance at the Highways, Cipta Karya and Spatial Planning Services. (6) Work Stress is accepted/mediated by Work Load on Employee Performance. (7) Work Stress is accepted/mediated by Work Environment on Employee Performance.